Co-evolution between Stages of Institutionalization and Agency: The Case of the Music Industry’s Business Model - Moyon, Emilien; Lecocq, Xavier (Management international / Gestiòn Internacional / International Management, 2010)
The relationship between structure and agency is a central issue in studying change. The aim of this paper is to focus on the interactions between the process of institutional change and the actors’ strategic behaviour. Based on research on the music industry, we observed co-evolution between the actor level and the organizational field level by identifying three consequences of the incumbents’ actions on the institutional change process (alternative practices selection, alternative practices modification and process duration) and three consequences of coercive pressures on agency (strategic adjustment, traditional practices modification and legitimization).